A new species of stygobitic isopod (Crustacea: Isopoda) of the genus Mexistenasellus from Veracruz, Mexico - Fernando Álvarez Noguera; Antonio Guillén-Servent (Revista Mexicana de Biodiversidad)
A new species of stygobitic isopod from Cerro Colorado Cave, Municipality of Apazapan, near Xalapa, Veracruz, is described. The new species is placed in Mexistenasellus due to the lack of eyes and pigmentation, a head distinct from pereonite 1, and 2 well developed pleonites. Other characters, such as the number of setae in the dactyli of the pereiopods, show slight variations from the original description of the genus. The new species can be distinguished from the previously known 7 species in the genus by the shape of the head, the proportions of the pleotelson and length of uropods. Color in life is pink as is characteristic of the species of Mexistenasellus. A key to the species of Mexistenasellus is provided.